Des moyens de l’intégration monétaire européenne - Bourguinat, H. (L'Actualité économique)

(untitled) (HEC Montréal, 1973)
AbstractEuropean monetary integration policy nowadays centers on the search for a common money by opposition to a single monetary unit; but many problems remain as to the means of achieving this end.After reviewing the perennial discussions concerned with the foundations of this monetary integration (e.g. the problems of the optimum of a monetary area, where Mr. Bourguinat challenges the criteria based on differential factor mobility or on the relative degree of "openness"), the study analyses the narrowing of margins in the light of recent experience.Considering the events of 1972 and 1973 the narrowing of margins is a very difficult task; it means nothing less than creating for the E.E.C. members an island of stability in a world environment becoming evermore flexible.The freedom which has been lost on exchange rate fluctuations seems to have resulted in an increased instability of par values (e.g. the successive revaluations of the deutschmark, the florin, etc.).For the achievement of a truly common money the author suggests an alternative approach: it consists in issuing, side by side with national currencies, a unit called an Europa; serving initially as a unit of account, the Europa would gradually become a true means of payment.